summaryrefslogtreecommitdiff
path: root/Modules/_decimal/libmpdec/literature/matrix-transform.txt
blob: 701d85d6b43c8145b4d55ef841c4de9327bdeecf (plain)
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256


(* Copyright (c) 2011 Stefan Krah. All rights reserved. *)


The Matrix Fourier Transform:
=============================

In libmpdec, the Matrix Fourier Transform [1] is called four-step transform
after a variant that appears in [2]. The algorithm requires that the input
array can be viewed as an R*C matrix.

All operations are done modulo p. For readability, the proofs drop all
instances of (mod p).


Algorithm four-step (forward transform):
----------------------------------------

  a := input array
  d := len(a) = R * C
  p := prime
  w := primitive root of unity of the prime field
  r := w**((p-1)/d)
  A := output array

  1) Apply a length R FNT to each column.

  2) Multiply each matrix element (addressed by j*C+m) by r**(j*m).

  3) Apply a length C FNT to each row.

  4) Transpose the matrix.


Proof (forward transform):
--------------------------

  The algorithm can be derived starting from the regular definition of
  the finite-field transform of length d:

            d-1
           ,----
           \
    A[k] =  |  a[l]  * r**(k * l)
           /
           `----
           l = 0


  The sum can be rearranged into the sum of the sums of columns:

            C-1     R-1
           ,----   ,----
           \       \
         =  |       |  a[i * C + j] * r**(k * (i * C + j))
           /       /
           `----   `----
           j = 0   i = 0


  Extracting a constant from the inner sum:

            C-1           R-1
           ,----         ,----
           \             \
         =  |  r**k*j  *  |  a[i * C + j] * r**(k * i * C)
           /             /
           `----         `----
           j = 0         i = 0


  Without any loss of generality, let k = n * R + m,
  where n < C and m < R:

                C-1                          R-1
               ,----                        ,----
               \                            \
    A[n*R+m] =  |  r**(R*n*j) * r**(m*j)  *  |  a[i*C+j] * r**(R*C*n*i) * r**(C*m*i)
               /                            /
               `----                        `----
               j = 0                        i = 0


  Since r = w ** ((p-1) / (R*C)):

     a) r**(R*C*n*i) = w**((p-1)*n*i) = 1

     b) r**(C*m*i) = w**((p-1) / R) ** (m*i) = r_R ** (m*i)

     c) r**(R*n*j) = w**((p-1) / C) ** (n*j) = r_C ** (n*j)

     r_R := root of the subfield of length R.
     r_C := root of the subfield of length C.


                C-1                             R-1
               ,----                           ,----
               \                               \
    A[n*R+m] =  |  r_C**(n*j) * [ r**(m*j)  *   |  a[i*C+j] * r_R**(m*i) ]
               /                     ^         /
               `----                 |         `----    1) transform the columns
               j = 0                 |         i = 0
                 ^                   |
                 |                   `-- 2) multiply
                 |
                 `-- 3) transform the rows


   Note that the entire RHS is a function of n and m and that the results
   for each pair (n, m) are stored in Fortran order.

   Let the term in square brackets be f(m, j). Step 1) and 2) precalculate
   the term for all (m, j). After that, the original matrix is now a lookup
   table with the mth element in the jth column at location m * C + j.

   Let the complete RHS be g(m, n). Step 3) does an in-place transform of
   length n on all rows. After that, the original matrix is now a lookup
   table with the mth element in the nth column at location m * C + n.

   But each (m, n) pair should be written to location n * R + m. Therefore,
   step 4) transposes the result of step 3).



Algorithm four-step (inverse transform):
----------------------------------------

  A  := input array
  d  := len(A) = R * C
  p  := prime
  d' := d**(p-2)             # inverse of d
  w  := primitive root of unity of the prime field
  r  := w**((p-1)/d)         # root of the subfield
  r' := w**((p-1) - (p-1)/d) # inverse of r
  a  := output array

  0) View the matrix as a C*R matrix.

  1) Transpose the matrix, producing an R*C matrix.

  2) Apply a length C FNT to each row.

  3) Multiply each matrix element (addressed by i*C+n) by r**(i*n).

  4) Apply a length R FNT to each column.


Proof (inverse transform):
--------------------------

  The algorithm can be derived starting from the regular definition of
  the finite-field inverse transform of length d:

                  d-1
                 ,----
                 \
    a[k] =  d' *  |  A[l]  * r' ** (k * l)
                 /
                 `----
                 l = 0


  The sum can be rearranged into the sum of the sums of columns. Note
  that at this stage we still have a C*R matrix, so C denotes the number
  of rows:

                  R-1     C-1
                 ,----   ,----
                 \       \
         =  d' *  |       |  a[j * R + i] * r' ** (k * (j * R + i))
                 /       /
                 `----   `----
                 i = 0   j = 0


  Extracting a constant from the inner sum:

                  R-1                C-1
                 ,----              ,----
                 \                  \
         =  d' *  |  r' ** (k*i)  *  |  a[j * R + i] * r' ** (k * j * R)
                 /                  /
                 `----              `----
                 i = 0              j = 0


  Without any loss of generality, let k = m * C + n,
  where m < R and n < C:

                     R-1                                  C-1
                    ,----                                ,----
                    \                                    \
    A[m*C+n] = d' *  |  r' ** (C*m*i) *  r' ** (n*i)   *  |  a[j*R+i] * r' ** (R*C*m*j) * r' ** (R*n*j)
                    /                                    /
                    `----                                `----
                    i = 0                                j = 0


  Since r' = w**((p-1) - (p-1)/d) and d = R*C:

     a) r' ** (R*C*m*j) = w**((p-1)*R*C*m*j - (p-1)*m*j) = 1

     b) r' ** (C*m*i) = w**((p-1)*C - (p-1)/R) ** (m*i) = r_R' ** (m*i)

     c) r' ** (R*n*j) = r_C' ** (n*j)

     d) d' = d**(p-2) = (R*C) ** (p-2) = R**(p-2) * C**(p-2) = R' * C'

     r_R' := inverse of the root of the subfield of length R.
     r_C' := inverse of the root of the subfield of length C.
     R'   := inverse of R
     C'   := inverse of C


                     R-1                                      C-1
                    ,----                                    ,----  2) transform the rows of a^T
                    \                                        \
    A[m*C+n] = R' *  |  r_R' ** (m*i) * [ r' ** (n*i) * C' *  |  a[j*R+i] * r_C' ** (n*j) ]
                    /                           ^            /       ^
                    `----                       |            `----   |
                    i = 0                       |            j = 0   |
                      ^                         |                    `-- 1) Transpose input matrix
                      |                         `-- 3) multiply             to address elements by
                      |                                                     i * C + j
                      `-- 3) transform the columns



   Note that the entire RHS is a function of m and n and that the results
   for each pair (m, n) are stored in C order.

   Let the term in square brackets be f(n, i). Without step 1), the sum
   would perform a length C transform on the columns of the input matrix.
   This is a) inefficient and b) the results are needed in C order, so
   step 1) exchanges rows and columns.

   Step 2) and 3) precalculate f(n, i) for all (n, i). After that, the
   original matrix is now a lookup table with the ith element in the nth
   column at location i * C + n.

   Let the complete RHS be g(m, n). Step 4) does an in-place transform of
   length m on all columns. After that, the original matrix is now a lookup
   table with the mth element in the nth column at location m * C + n,
   which means that all A[k] = A[m * C + n] are in the correct order.


--

  [1] Joerg Arndt: "Matters Computational"
      http://www.jjj.de/fxt/
  [2] David H. Bailey: FFTs in External or Hierarchical Memory
      http://crd.lbl.gov/~dhbailey/dhbpapers/